Cobalta‐Electrocatalyzed C−H Activation in Biomass‐Derived Glycerol: Powered by Renewable Wind and Solar Energy - Meyer, Tjark H. (ChemSusChem, 2020)
Aqueous glycerol was identified as a renewable reaction medium for metalla‐electrocatalyzed C−H activation powered by sustainable energy sources. The renewable solvent was employed for cobalt‐catalyzed C−H/N−H functionalizations under mild conditions. The cobalta‐electrocatalysis manifold occurred with high levels of chemo‐ and positional selectivity and allowed for electrochemical C−H activations with broad substrate scope. The resource economy of this strategy was considerably substantiated by the direct use of renewable solar and wind energy.